Surface modification of polyethylene terephthalate films by direct fluorination - Yaqiang Liu; Qingqing Chen; Xuelian Du; Liqiang Li; Peng Li (AIP Advances, 2018)
Polyethylene terephthalate (PET) films were surface fluorinated in a reaction kettle using a F2/N2 blend with 12.5% F2 by volume for the different time of 15, 30, 60, and 90 min at the same temperature of 30 °C. The chemical composition, surface morphology, wettability and thermal properties were characterized by attenuated total reflection fourier transform infrared spectroscopy (ATR-IR), field emission scanning electron microscopy (FE-SEM), contact angle and surface energy measurement, and thermogravimetry-differential thermal analysis (TG–DTA). It is found that surface chemical composition and structure was substantially altered due to fluorination and surface morphology evolved continuously with fluorination time. The results indicate that the surface hydrophilicity of the fluorinated PET films is much higher than that of the unfluorinated PET films and increases significantly with fluorination time, as the fluorination led to a large decrease in water contact and a dramatic increase in surface energy. An increase in the number of polar groups is regarded as the main reason for the increases of hydrophilicity with fluorination time. The surface fluorination causes a slight decrease in the thermal stability of PET films because of the introduction of chain scission.